Człowiek z laską na tle orła na fryzie synagogi z Korazin w Galilei - Szkołut, Paweł (Vox Patrum, 2002)
A frieze of the synagogue in Korazin displays a half-lying man with a stuff in his hand, reaching for a bunch of grapes - with the eagle in the background. The aim of this article is a description and interpretation of the relief in the broad context of other motifs and narrative scenes on the frieze. Although at present time the relief is preserved in a very damaged State, its interpretation has been conducted on the basis of the State of maintenance recorded on a photography from the beginning of the XX-th century.